2018
DOI: 10.2196/preprints.10090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

User-driven comments on a Facebook advertisement recruiting Canadian parents in a study on immunization: Content Analysis (Preprint)

Abstract: Background: More people are searching for immunization information online and potentially being exposed to misinformation and anti-vaccine sentiment via content and discussions on social media platforms. As vaccination coverage rates remain sub-optimal in several developed countries, and outbreaks of vaccine preventable diseases [VPDs] become more prevalent, it is important that we build on previous research by analyzing themes in online vaccination discussions, including those that individuals may see without… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Many of the comments that directed blame attributions at a societal level focused on 'big pharma' trying to make money and hide natural treatments and cures for cancer. These results were similar to a recent study which also found a theme of distrust in pharmaceutical companies on Facebook posts about immunisations (Tustin et al, 2018). Other environmental causes for cancer such as chemical exposure and air pollution were also mentioned in comments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many of the comments that directed blame attributions at a societal level focused on 'big pharma' trying to make money and hide natural treatments and cures for cancer. These results were similar to a recent study which also found a theme of distrust in pharmaceutical companies on Facebook posts about immunisations (Tustin et al, 2018). Other environmental causes for cancer such as chemical exposure and air pollution were also mentioned in comments.…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, sharing advice in Facebook comments has the potential to help other people with cancer and to enable them to build a network of support however, on the other hand, there is potential for dangerous misinformation to be spread. Although the current study did not measure comments in terms of accuracy, a recent study on immunisation posts on Facebook found that 20.8% of negative comments contained inaccurate knowledge (Tustin et al, 2018). This is particularly concerning given that previous research shows that people may trust other responders more than the advice from the media .…”
Section: Discussionmentioning
confidence: 71%
“…The overarching beliefs discovered primarily included a distrust of the scientific community and pharmaceuticals, and the presence of superstitious and conspiratorial beliefs (Smith et al, 2004;Fowler et al, 2006;Wada and Smith, 2015;Chung et al, 2017;Carrion, 2018;Hornsey et al, 2018;Tustin et al, 2018;Bianco et al, 2019;Helps et al, 2019;Romijnders et al, 2019;Smith and Graham, 2019;Cadeddu et al, 2020;Tomljenovic et al, 2020;Dzieciolowska et al, 2021;Martinez-Berman et al, 2021;Motta et al, 2021;Murphy et al, 2021;Rozbroj et al, 2022). This finding is congruent with previous research exploring linguistic themes among social media users expressing anti-vaccination beliefs (Buchanan and Beckett, 2014;Faasse et al, 2016;Okuhara et al, 2017Okuhara et al, , 2018Smith and Graham, 2019;Dhaliwal and Mannion, 2020).…”
Section: Beliefssupporting
confidence: 82%
“…All studies included in the review were conducted between 2004 and 2021. The number of studies investigating the underlying mechanisms of anti-vaccination attitudes and beliefs was 33 (Smith et al, 2004;Fowler et al, 2006;Luyten et al, 2014;Michael et al, 2014;Wada and Smith, 2015;Reich, 2016;Amin et al, 2017;Chung et al, 2017;Bryden et al, 2018;Carrion, 2018;Hornsey et al, 2018;Motta et al, 2018Motta et al, , 2021Restivo et al, 2018;Tustin et al, 2018;Bianco et al, 2019;Carpiano et al, 2019;Helps et al, 2019;Romijnders et al, 2019;Rossen et al, 2019;Rozbroj et al, 2019aRozbroj et al, , 2020Rozbroj et al, , 2022Cadeddu et al, 2020;Goldberg and Richey, 2020;Tomljenovic et al, 2020;Dzieciolowska et al, 2021;Elkalmi et al, 2021;Freeman et al, 2021;Huynh and Senger, 2021;Martinez-Berman et al, 2021;Murphy et al, 2021). Within this subset of studies, 12 studies investigated parents as a sample (Smith et al, 2004;Reich, 2016;Amin et al, 2017;Chung et al, 2017;Carrion, 2018;Tustin et al, 2018;Bianco et al, 2019;Carp...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation